2014
DOI: 10.1108/jpif-01-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency in commercial buildings: capturing added-value of retrofit

Abstract: Purpose – The purpose of this paper is to investigate, the functioning of value creating configurations and stakeholder interactions in networks of organisations of the retrofit industry for commercial buildings. Design/methodology/approach – A value approach was applied to develop a model of retrofit activities. A Europe wide stakeholder engagement, consisting of over 50 face-to-face interviews with key informants with energy efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…To avoid misunderstandings, each part of the phrases is connected by a hyphen. Improvements which can be applied to save energy in buildings can be reached, for instance with energy efficiency measurements such as optimised insulation building retrofit [29]. The focus of the optimisation of a whole city quarter's energy technology network needs to be extended from single house level to building groups.…”
Section: Smart Energy Planningmentioning
confidence: 99%
“…To avoid misunderstandings, each part of the phrases is connected by a hyphen. Improvements which can be applied to save energy in buildings can be reached, for instance with energy efficiency measurements such as optimised insulation building retrofit [29]. The focus of the optimisation of a whole city quarter's energy technology network needs to be extended from single house level to building groups.…”
Section: Smart Energy Planningmentioning
confidence: 99%
“…The use of consultant for reducing energy use in commercial and educational buildings also plays a significant role. Its intervention to green building concept is delivered by the use of some green rating tools and instruments [4,5,6,7]. In term of design, the use of passive solar heat gain techniques and components, building orientation and position on site, glazing techniques, play the very important part in defining building's green methods.…”
Section: Related Studiesmentioning
confidence: 99%
“…The second topic, which has seen slightly more attention in line with developers and investors, is the sustainable adaptation, redevelopment or retrofitting of real estate (Morrissey et al, 2014;Wilkinson, 2012;Schwede et al, 2008;Wilkinson et al, 2009;Bullen, 2007). Although there is a little work relating to occupiers, Miller & Buys (2008) concluded that for tenants, sustainability was an abstract concept, and was also linked to the size of the organisation in the building.…”
Section: 'Going Green': Occupiers' Role In the Performance Of Sustainmentioning
confidence: 99%